Asynchronous stochastic approximations with asymptotically biased errors and deep multi-agent learning - Ramaswamy, Arunselvan; Bhatnagar, Shalabh; Quevedo, Daniel E (IEEE Transactions on Automatic Control)

Interlaboratory study on rheological properties of cement pastes and reference substances: comparability of measurements performed with different rheometers and measurement geometries - Haist, Michael; Link, Julian; Nicia, David; Leinitz, Sarah; Baumert, Christian; von Bronk, Tabea; Cotardo, Dario; Eslami Pirharati, Mahmoud; Fataei, Shirin; Garrecht, Harald; Gehlen, Christoph; Hauschildt, Inga; et al. (Materials and Structures)
Abstract This paper presents the results of an interlaboratory study of the rheological properties of cement paste and ultrasound gel as reference substance. The goal was to quantify the comparability and reproducibility of measurements of the Bingham parameters yield stress and plastic viscosity when measured on one specific paste composition and one particular ultrasound gel in different laboratories using different rheometers and measurement geometries. The procedures for both in preparing the cement paste and carrying out the rheological measurements on cement paste and ultrasound gel were carefully defined for all of the study’s participants. Different conversion schemes for comparing the results obtained with the different measurement setups are presented here and critically discussed. The procedure proposed in this paper ensured a reasonable comparability of the results with a coefficient of variation for the yield stress of 27% and for the plastic viscosity of 24%, despite the individual measurement series’ having been performed in different labs with different rheometers and measurement geometries.

Stabilization of polyacrylonitrile nanofiber mats obtained by needleless electrospinning using dimethyl sulfoxide as solvent - Moritzer, Elmar; Wortmann, M.; Sabantina, L.; Klocker, M.; Mirasol, JR (JOURNAL OF INDUSTRIAL TEXTILES)

2K-Haftverbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Lochbaum, Ella (Plastverarbeiter)

Additive Manufactured Heat Pipe Injection Mould Element - Moritzer, Elmar; Kartelmeyer, Stephan; Hüttemann, Vincent (Direct Digital Manufacturing Conference 2020)

Additiveteile Direktverschrauben - Moritzer, Elmar; Hillemeyer, Johannes (6. Fachkonferenz 3D-Druck in der Automobielindustrie)

ANALYSIS OF THE ADVANTAGEOUS PROCESS AND MIXING BEHAVIOUR OF WAVE-DISPERSION SCREWS IN SINGLE SCREW EXTRUSION - Schöppner, Volker; Dörner, M.; Marschik, C.

Ansatz zur sicheren Direktverschraubung additiv gefertigter Einschraubtuben - Moritzer, Elmar; Hillemeyer, Johannes (10. Gemeinschaftskolloquium)

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part B. (Superimposed Drag-Pressure Flows in Extrusion) - Schöppner, Volker; Dörner, M.; Marschik, C.; Roland, W.; Schaufler, S.; Steinbichler, G. (Polymers)

CONTEXT OF FIBER LENGTH DISTRIBUTION, HOMOGENEITY AND MECHANICAL PROPERTIES IN DIRECT COMPOUNDING INJECTION MOLDING OF FIBER REINFORCED THERMOPLASTICS - Moritzer, Elmar; Wittke, M. (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

Development of a New Joining Technology for Hybrid Joints of Sheet Metal and Continuous Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Krassmann, Dimitri (73rd Annual Assembly of the International Institute of Welding (IIW))

Development of an Analytical Model to Describe the Disperse Melting in Wave-Dispersion Screws - Schöppner, Volker; Dörner, M.; Marschik, C.; Steinbichler, G. (Polymers)

Die Kunst der Entformung - Moritzer, Elmar; Jilg, J.; Schilp, C.; Krempl, N.; Friesenbichler, W. (Kunststoffe)

EINSATZ VON MASCHINELLEM LERNEN FÜR DIE REZYKLAT-VERARBEITUNG - Moritzer, Elmar; Hopp, Matthias; Wittke, Marius (WAK Jahreszeitschrift)

Entwicklung einer neuartigen Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Krassmann, Dimitri (Joining Plastics)

Entwicklung eines Spritzgießsonderverfahrens zur Herstellung von Hybridbauteilen aus faserverstärkten Thermoplasten und Metallblechen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (10. Fügetechnisches Gemeinschaftskolloquium)

INJECTION MOLD COOLED WITH ADDITIVE MANUFACTURED HEAT PIPE CORE-ELEMENT - Moritzer, Elmar; Kartelmeyer, S.; Hüttemann, M.; Jaroschek, C. (78th Annual Technical Conference for Plastics Professionals (ANTEC))

Inline Surface Activation in the multi Injection Molding Process - Moritzer, Elmar; Mühlhoff, Frederik Marvin (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

InMould-Plasma Technologie - Dauerhaft beständige 2K-Verbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Lochbaum, Ella; Krampe, Erhard (KGK - Rubberpoint)

An apparatus to synthesize ceramic nanoparticles with a precisely adjusted temperature history and a significant mass output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)